A Schematic Two Overlapping-Band Model for Superconducting Sulfur Hydrides: The Isotope Mass Exponent - R. M. Méndez-Moreno (Advances in Condensed Matter Physics)
The high value of the isotope shift in sulfur hydrides supports a phonon-mediated pairing scenario of superconductivity for these high-temperature superconductors which are consistent with the Bardeen–Cooper–Schrieffer (BCS) framework. Knowing that a large electronic density of states enhances the critical temperature (Tc), generalized Fermi surface topologies are used to increase it. A multicomponent model within the BCS framework is proposed in this work for sulfur hydride superconductors. This model is used to evaluate some properties of the H3S superconductor. Strong and intermediate coupling effects are taken into account with the effective McMillan approximation, and the isotope coefficient is evaluated as a function of the coupling parameter as well as other relevant parameters of the model.